PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, PROGRAM K3 TERHADAP KEPUASAN KERJA KARYAWAN - Kurniawati, I Gst. Ayu Ngr. Pradnya; Sariyathi, Ni Ketut (E-Jurnal Manajemen, 2015)
The study was conducted in order to determine the effect of communication, leadership and compensation simultaneously and partially on employee job satisfaction, as well as where the dominant variable affecting job satisfaction of employees in PT BPR Nusamba Mengwi. Census method used to determine the number of samples is 45 employees. Interview, observation and questionnaire used in data collection. Data were analyzed using confirmatory factor analysis and multiple linear regression analysis. The results were obtained conclusion that communication, leadership and compensation simultaneously and partially positive and significant effect on employee job satisfaction, where compensation is variable dominant effect .
Keywords: kepemimpinan; budaya organisasi; program K3; kepuasan kerja